Implementasi Augmented Reality Pada Pengenalan Alat Peraga IPA Dengan Metode Marker Based Tracking - Nadhifa, Nanda; Hidayat, Taufik; Sofyan, Asep Abdul (Universitas Islam Syekh Yusuf, 2022)
Science teaching aids are objects or tools used for teaching and learning activities in elementary schools, or other purposes as real objects that are made intentionally to develop concepts in learning that help learning more effectively. Science teaching aids can be developed with Augmented Reality technology. Augmented Reality is a technological development that combines the virtual world with the real world that is built into three-dimensional (3D) objects. Which is Augmented Reality as a learning medium that aims to increase student interest in learning. The Augmented Reality method used is Marker Based Tracking with pictures of science teaching aids using the ISO 9126 testing method and questionnaire testing, which is used to generate calculations to show that the application of science teaching aids is able to make students more interested in learning. From the results of the implementation of augmented reality, the resulting learning media for science teaching aids are presented in the form of information that can be displayed in writing or audio with the help of an android smartphone in order to increase student interest in learning.